WATER CONSUMPTION OF OILSEED FLAX UNDER THE INFLUENCE OF PLANT GROWTH REGULATORS WITH DIFFERENT METHODS OF MAIN TILLAGE IN THE CONDITIONS OF THE SOUTHERN STEPPE OF UKRAINE (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
According to the results of the three-year research, the influence of the methods of basic soil cultivation and the use of growth regulators on water consumption and yield of Vodohrai oilseed flax was determined.Statement of the problem. Determining the optimal method of basic tillage, as an important measure for the accumulation of moisture in the soil, in combination with the use of plant growth regulators when growing new varieties of oilseed flax is an essential factor that makes it possible to reduce fluctuations in its yield depending on the level of moisture availability of crops in the arid conditions of the Ukrainian Steppe, by optimizing the combined action of agricultural techniques.Purpose of the research was to establish the characteristics of water consumption of Vodogray oilseed flax under the influence of the main tillage methods and the use of plant growth regulators in the conditions of the Southern Steppe of Ukraine.Research methods. The experiment was conducted in 2011-2013 at the experimental field of the Institute of Oilseed Crops of the Zaporizhia District of the Zaporizhia Region. A two-factor field experiment was established to solve the tasks. Factor A – method of basic soil cultivation (3 options). Factor B – use of growth regulators (4 options). The total number of options in the experiment was 12. Repetition was three times. Setting up the experiment and accounting, measurements, and accompanying observations were carried out according to the methods of field experiments. Total water consumption was calculated using the water balance method.Research results. Depending on the method of the main soil cultivation, the total moisture reserves in the soil layer at 0-100 cm at the beginning of the growing season were equal to: 278.2 mm for plowing; 274.8 mm for conservation deep tillage and 270.9 mm for conservation shallow tillage. In relation to plowing, the reserves decreased by 3.6 mm for conservation deep tillage and 7.3 mm for conservation shallow tillage. The amount of precipitation, taking into account the ratio of use on average for three years of the vegetation period was 68.2 mm.The moisture reserves at the end of the growing season were greater under conservation deep tillage – 157.9-162.5 mm. During plowing, they decreased by 1.0-2.0 mm. The smallest moisture reserves at the end of the growing season, 156.2-161.2 mm, were noted for shallow tillage without harrowing. The use of growth regulators led to a decrease in moisture reserves at the end of the growing season of oilseed flax by: 2.4-4.8 mm for plowing; 1.3-4.6 mm for conservation deep tillage and 2.2-5.0 mm for conservation shallow tillage.The highest total water consumption per crop (189.8 mm) was recorded for plowing with application of Agrobak plus to the soil + seed treatment with Agrobak plus for seeds + treatment during vegetation (preflowering stage) with a tank mixture of Agrobak plus and Rostkoncentrat. The use of growth regulators contributed to an increase in total water consumption by: 2.4-4.8 mm for plowing; 1.3-4.6 mm for conservation deep tillage and 2.2-5.0 mm for conservation shallow tillage.The highest yield of flax of the Vodohrai oil variety – 1.45 t/ha was obtained for plowing cultivation with application of Agrobak plus to the soil + seed treatment with Agrobak plus for seeds + treatment during vegetation (preflowering stage) with a tank mixture of Agrobak plus and Rostkoncentrat. The yield increase from the use of growth regulators was equal to: for plowing 0.06-0.19 t/ha; for conservation deep tillage 0.04-0.16 t/ha; for conservation shallow tillage 0.05-0.14 t/ha.Conclusions. The lowest ratio of water consumption (1309 m3/t) was noted for the cultivation of oil flax of the Vodohrai variety by plowing with application of Agrobak plus to the soil + seed treatment with Agrobak plus for seeds + treatment during vegetation (preflowering stage) with a tank mixture of Agrobak plus and Rostkoncentrat. The use of growth regulators contributed to the reduction of the water consumption coefficient for plowing by 48-159 m3/t; for conservation deep tillage by 42-157 m3/t and for conservation shallow tillage by 49-136 m3/t.
Keywords: main tillage; oilseed flax; plant growth regulator; total water consumption; productivity; water consumption ratio